Drug eluting stents versus bare metal stents in coronary artery disease patients: outcomes and complications - Kalburgi, Veeraj (International Journal of Research in Medical Sciences, 2018)
Background: To date, data regarding the long-term safety and efficacy of BMS and DES implantation in a real-world population are limited. Thus, this study was designed to study the complications, early and late outcomes of drug-eluting stents (DES) versus bare metal stents (BMS) after implantation in coronary artery disease (CAD) patients up to 6months follow-up period. Methods: This was a single-center, hospital-based, prospective study conducted at a tertiary care center in India. Records of 250 patients who underwent percutaneous coronary intervention (PCI) in the period of January to December 2007 were included in the study. Early outcomes were indications of coronary angioplasty, length of hospital stay, Killip’s classification at presentation, type of coronary lesions, cath-lab outcomes and acute stent thrombosis (ST). Patients were clinically followed-up till hospital discharge, 30days and in 6months. Results: Total 250 patients with an age range of 30-39years underwent PCI. Of the study population who underwent PCI 111 patients (44.4%) received DES, 104 patients (8%) received BMS, 20 patients received both DES and BMS and 15 patients underwent POBA, respectively. Complications like stroke and major bleeding were observed in 2 patients (0.8%) and 12 patients (4.8%) respectively. TIMI III flow and ST was observed in 215 patients (91.5%) and 6 patients (2.6%), respectively. Death was observed in 3 patients (1.2%) due to cardiogenic shock. Conclusions: DES and BMS have good procedural success in achieving early revascularization with PCI. The incidence of ST was almost equal in DES compared to BMS.